TOURISTS EXPECTATION AND PERCEPTION TOWARD SANGEH TOURISM VILLAGE - I Made Bayu Wisnawa; Anak Agung Ratih Wijayanti; Sulistyoadi Jokosaharjo (Journal of Business on Hospitality and Tourism, 2019)
Sangeh is a tourism village which has tourism potentials such as nature scenery, rice field, forest, and culinary. This research studies the expectation and perception of the tourists who visit Sangeh. A qualitative method using questionnaire and interview techniques was used in the research. There were 155 respondents in which the questionnaire was distributed offline and online.  This research aims to find out the expectation, perception, and satisfaction of the tourists in enjoying their tourism visit in Sangeh, and also to find out the efforts which can be done by the management in increasing tourists’ satisfaction in enjoying the tourism visit. The results show that the tourists’ expectation is on the installation of road signs which enable them to reach Sangeh easily. The highest perception felt by the tourists is its beautiful natural scenery. The biggest gap felt by the tourists is the internet connection. The effort which should be done by the management is by providing additional supporting facilities.